A Para-text Driven Back-translating of the Diamond Sutra from English to Chinese (Asian Journal of Social Science Studies, 2016)
This thesis is to analyze problems arising out of the rendition of the Sutra, such as limited preparation, time management, knowledge background and translation skills used during the translating process. Psychological aspect of the translator is also discussed in this thesis, esp. the contradiction between the Buddhistic teachings, vegetarianism and physical strength of the translator plus a solution. Cultural aspect of translation is also considered in the thesis. The results of the experience are: knowledge background is the premise to select the best original and pull through the translating; the translator’s traits might have a say in the translating dynamics; time management is significantly important in translation; contradicting elements might be resolved by psychological meditation; translating tools and tactics might affect the speed of translation while translation strategy might have an over-riding role during the translation through solving contradiction between ethics and strategy; in turn, the choice is to further clarify the definition of translation and interpretation as a whole.